COVID‐19; current situation and recommended interventions. Issue 5 (14th January 2021) - Saeed, Haitham; Osama, Hasnaa; Madney, Yasmin M.; Harb, Hadeer S.; Abdelrahman, Mona A.; Ehrhardt, Carsten; Abdelrahim, Mohamed E. A.
Abstract: Background: The new coronavirus (SARS‐COV‐2) that emerged at the end of 2019 was stated in China and infected millions of people around the world, with the highest spread rate amongst humans compared with other coronaviruses. This paper aimed to review and analyse the published studies about COVID‐19 diagnosis, prevention, and treatment. Method: The reviewed studies were clinical trials, in‐vivo, in‐vitro, guidelines, reports from the world health organization (WHO), and the centre for disease control and prevention (CDC) in addition to systemic reviews. All data extracted and analysed to stand on the latest updates and recommendations for fighting this severe attack of COVID‐19. Results: Most important antiviral therapy of COVID‐19 clinical trials is still running without clear results, but a few trials have indicated the role of numerous drugs in the treatment of COVID‐19. Specific recommendations for aerosol therapy should be followed for the management of COVID‐19. Conclusion: Nature of COVID‐19 is still not very clear, however, management of the condition is similar to the previous attacks of coronaviruses.